Child protection in Bangladesh: An analysis of regulatory framework and future reforms - Islam, Md. Zahidul; Mia, Md. Tuhin (2021)
Extreme acts and cruel treatment of children deprive them of their rights. Reliable and constant evidence from many countries shows that children are continuing to face brutal abuse, exploitation and distortive practices continue to happen despite the existence of laws which aims at protecting them. In fact, this remains mostly invisible. This study tries to draw attention regarding brutal behaviour towards children and major concerns on the need for regulatory changes. The reason for this study is to assess the role of existing laws in defending children rights in Bangladesh. Besides, the article aims to gain a deeper understanding of the present legal protection of children and how future reforms can be done. In addition, efforts have been made to study the various parts of children’s rights, which will affect the children-friendly environment. Secondary sources textbook, journal articles and case commentaries are used to examine the guarantee of children rights and to evaluate the applicability of laws within the country. The results of the study show that although there are several laws and policies to protect children in Bangladesh, children are still being exploited and ill-treated. Therefore, legal reforms should be introduced to combat the situation.